Beginning Python from novice to professional - Hetland, Magnus Lie; Nelli, Fabio (Apress, 2024)
Gain a fundamental understanding of Python's syntax and features with this revised introductory and practical reference. Covering a wide array of Python-related programming topics, including addressing language internals, database integration, network programming, and web services, you'll be guided by sound development principles. Updated to reflect the latest in Python programming paradigms and several of the most crucial features found in Python 3, Beginning Python, Fourth Edition also covers advanced topics such as extending Python and packaging/distributing Python applications. Ten accompanying projects will ensure you can get your hands dirty in no time.
Includes bibliographical references and index
Keywords: Python (Computer program language); Computer programming; Python (Langage de programmation); Programmation (Informatique); computer programming